Synthesis of N-acetyl diazocine derivatives via cross-coupling reaction - Brandt, Thomas; Lentes, Pascal; Rudtke, Jeremy; Hösgen, Michael; Näther, Christian; Herges, Rainer (Beilstein Journal of Organic Chemistry, 2025)
Diazocines are photoswitches derived from azobenzenes by bridging the two phenyl rings in ortho position with a CH2CH2 group forming an eight membered (diazocine) ring. Diazocine is superior to most azobenzenes in almost all photophysical properties (switching efficiency, quantum yield, wavelengths etc.). The biggest advantage, especially in photopharmacology and when used in photoswitchable materials, is the inverted thermodynamic stability of the two switching states (isomers). The Z isomer is more stable than the E form. However, one disadvantage that it shares with the frequently used azobenzene is that the switching efficiency decreases sharply with increasing water content in the solvent. In a recently published paper, we reported that replacing one CH2 group in the bridge with NCOCH3 not only confers intrinsic water solubility, but also largely eliminates the problem of reduced switching efficiency in aqueous solutions. In order to investigate the chemistry of this promising photoswitch and to unlock further applications, we now investigate strategies for the synthesis of derivatives, which are based on cross-coupling reactions. Fourteen vinyl-, aryl-, cyano-, and amino-substituted diazocines were prepared via Stille, Suzuki, and Buchwald–Hartwig reactions. X-ray structures are presented for derivatives 1, 2 and 7.
Keywords: cross-coupling; diazocine; N-acetyl diazocine; photoisomerization; photoswitch; thermal relaxation